Technological tool for the development of value chains of the cultural industry of Cali - Guapacha Arango , Juan Camilo
This article proposes as a dynamic strategy for the cultural sector of Cali: the creation of a web platform that allows the different actors (public, artists, artisans, managers, etc.), the use of technological tools to improve efficiency and agility in marketing and dissemination processes. Characteristics of the city's cultural market, some effects of the social crisis derived from the measures imposed to contain the spread of the SARS-CoV-2 virus and the social interaction of people with electronic devices to acquire cultural or entertainment content are analyzed. Surveys were applied and interviews were carried out to address the responses in more depth, what was observed in the different spaces of confluence of actors in the sector was recorded in an anecdotary, which allowed having information for analysis from different sources. A high percentage of those consulted claimed to have used an electronic medium at least once in their lives to purchase a product or service from the cultural sector of Cali, but as a paradox, many claimed to be unaware of the city's cultural offerings, stating that they finds a lot of fragmented information, which does not allow easy identification according to interests; For this reason, it is extremely important to centralize a large part of the offer and information of the cultural industry in a virtual space, which serves to market and disseminate, with the option of segmenting interests to facilitate the task of buying products and services.